ANALISIS MINAT BELAJAR DAN GAYA BELAJAR SELAMA PANDEMI COVID-19 SISWA KELAS V SDN 3 CIKEMBULAN KECAMATAN PEKUNCEN KABUPATEN BANYUMAS TAHUN AJARAN 2020/2021 - Purnama, Marita Cahya; Suryandari, Kartika Chrysti; Suhartono, Suhartono Suhartono (Universitas Sebelas Maret, 2021)
Studying from home during the Covid-19 pandemic is more effective if the teacher concerns the student’s interest in learning and learning styles. The study aimed to analyze student’s interest in learning and learning styles and to describe factors influencing interest in learning and learning styles to fifth grade students at SD Negeri 3 Cikembulan during the Covid-19 pandemic. It was qualitative with narrative design. Data collection techniques used observation, interviews, and document studies. The observed aspects about interest in learning were fondness, interest, and student involvement while about learning styles were visual auditory, and kinesthetic. It concludes that student’s interest in learning is sufficient. The dominant student learning style is visual. Factors influencing interest in learning include talent, discipline, curiosity, concentration, learning needs, family, motivation, school, mass media, and society while factors influencing learning style include physical conditions, psychology, fatigue, family, school, and society.